Consumption, Public Disorder and the Politics of Knowing - Prashan Ranasinghe (lo Squaderno, 2011)
It is often said that we are what we consume. We are a consuming public, and a ravenously consuming one at that. We are, in other words, constituted by an ethic of consumption that is the hallmark of the world we live in (see Bauman, 2007; Hannigan, 1998; Zukin, 2004). This consuming ethic however, is not without criticism and has come under scrutiny from a variety of quarters. There is one in particular, which is not only a criticism of or about consumption, but also a reflection, even by-product, of it. This is the problem of visible poverty such as homelessness that pervades many large cities. In particular, many of the manifestations of visible poverty, what is often referred to as ‘public disorder’ – for example, panhandling, squeegeeing or loitering – are said to be of dire concern to consumption and the consumptive ethic.